Climate and stomatal traits drive covariation in nighttime stomatal conductance and daytime gas exchange rates in a widespread C4 grass. Issue 4 (4th November 2020) - Chieppa, Jeff; Brown, Tia; Giresi, Presley; Juenger, Thomas E.; Resco de Dios, Víctor; Tissue, David T.; Aspinwall, Michael J.
Summary: Nighttime stomatal conductance ( g sn ) varies among plant functional types and species, but factors shaping the evolution of g sn remain unclear. Examinations of intraspecific variation in g sn as a function of climate and co‐varying leaf traits may provide new insight into the evolution of g sn and its adaptive significance. We grew 11 genotypes of Panicum virgatum (switchgrass) representing differing home‐climates in a common garden experiment and measured nighttime and daytime leaf gas exchange, as well as stomatal density (SD) and size during early‐, mid‐, and late‐summer. We used piecewise structural equation modelling to determine direct and indirect relationships between home‐climate, gas exchange, and stomatal traits. We found no direct relationship between home‐climate and g sn . However, genotypes from hotter climates possessed higher SD, which resulted in higher g sn . Across genotypes, higher g sn was associated with higher daytime stomatal conductance and net photosynthesis. Our results indicate that higher g sn may arise in genotypes from hotter climates via increased SD. High SD may provide benefits to genotypes from hotter climates through enhanced daytime transpirational cooling or by permitting maximal gas exchange when conditions are suitable. These results highlight the role of climate and trait coordination in shaping genetic differentiation in g sn .